PROBLEMS OF MEMORIZING VOCABULARY IN FIFTH GRADE STUDENT IN LEARNING ARABIC AT MI MATHLA’UL ANWAR SRIRAHAYU REGENCY PRINGSEWU: Indonesia - Sholihah, Maratus; Al Ngarifin, Syeh; Muhtarom, Muhtarom (STIT Pringsewu, 2023)
Abstract Vocabulary is one of the elements of Arabic which is very important to be mastered by Arabic learners if they want to master the four language skills. One method for mastering mufrodat is by memorizing. The memorization method is also not an easy thing to practice, because memorizing requires more memory and patience and perseverance, so it is not uncommon for students, at the ibtidaiyah level, to experience problems in the process of memorizing the mufrodat. The type of research used is a qualitative approach, with a qualitative descriptive method. The results of research on the problems of memorizing mufrodat Arabic for Class V students in learning Arabic at MI Mathla'ul Anwar Srirahayu Pringsewu Regency are 1) some students are not fluent in reading Arabic script, 2) lack of motivation in memorizing mufrodat, 3) there is interference from outside such as disturbance from one classmate and commotion in the class. The solutions offered to be able to overcome these problems are 1) the teacher must play an active role in reciting Arabic script from mufrodat which students will memorize until all students know how to read it, 2) the teacher provides variations of techniques in memorizing mufrodat such as memorizing by singing, 3) the teacher provides motivation to memorize by giving gifts and punishments.